Emotional health outcomes are influenced by sexual minority identity and HIV serostatus. Issue 9 (2nd September 2021) - Nguyen, Annie L.; Sundermann, Erin; Rubtsova, Anna A.; Sabbag, Samir; Umlauf, Anya; Heaton, Robert; Letendre, Scott; Jeste, Dilip V.; Marquine, María J.
ABSTRACT: For people living with HIV (PLWH) and sexual minorities (SM), the intersection of identities can compound experiences like stigma and discrimination resulting in poor emotional health. We investigated the separate and interactive associations of HIV serostatus and sexual identity with emotional health. Our dataset included 371 participants. Emotional health was assessed by the NIH Toolbox emotion battery which yields negative affect, social satisfaction, and psychological well-being. Regressions were conducted for each composite, with HIV serostatus, sexual identity, and their interaction as independent variables along with covariates. The HIV serostatus x SM identity interaction was statistically significant in the regression of Negative Affect ( p = .01): heterosexuals living with HIV had worse Negative Affect compared to heterosexual HIV-persons ( p = .01). The interaction terms were for social satisfaction and psychological well-being were not significant. However, among PLWH, sexual minorities reported better Social Satisfaction ( p = .03) and marginally better psychological well-being ( p = .07) compared to heterosexuals.